2020
DOI: 10.1155/2020/8859251
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Coping Style on the Effects of Breath Count Mindfulness Training on Depressive Symptoms among International Students in China

Abstract: Mindfulness training has gained popularity in the scientific field and has been proposed as an efficient way for emotional regulation. Mindfulness-based cognitive therapy (MBCT) is designed especially for depressive people in reducing risk of depression relapse and is recommended in national guidelines as a treatment choice for relapse prevention in recurrent depression. The aim of the current study was to investigate the effects of mindfulness training on depressive symptoms of international students and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…This study found that the individual's intolerance to uncertainty (IU) plays a mediating role between loneliness and the individual's mental health during the COVID-19, that is, the higher the individual's loneliness, the more intolerable the uncertainty will be, and then the level of anxiety and depression will increase, as well as the stress sensitivity ( 48 ). Studies have found that loneliness and IU are the predictors of anxiety and depression, and loneliness is the strongest predictor, followed by IU ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the individual's intolerance to uncertainty (IU) plays a mediating role between loneliness and the individual's mental health during the COVID-19, that is, the higher the individual's loneliness, the more intolerable the uncertainty will be, and then the level of anxiety and depression will increase, as well as the stress sensitivity ( 48 ). Studies have found that loneliness and IU are the predictors of anxiety and depression, and loneliness is the strongest predictor, followed by IU ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it may be that loneliness during the COVID-19 makes individuals pay too much attention to themselves, triggering an unsuitable threat response; this response exacerbates the individual's intolerance to uncertainty, which causes anxiety and depression symptoms, and is more sensitive to stress. On the other hand, an individual's strategy for coping with uncertainty is usually to find social references to promote the individual's behavioral consistency with others ( 48 ), for example, the individual's behavioral manifestations are more herd behaviors. This can be seen from the crazy hoarding of daily necessities by ordinary people in various countries and the crazy spread of various rumors during the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…When incident occurs at work, mindfulness, as an important coping mechanism, will mobilize the internal strength to deal with negative emotions such as negativity, irritability, boredom and frustration, by which the negativity of the incidence could be reconstructed into positivity. Consequently, a more skilful approach and a new perspective could be utilizing (Ghawadra et al., 2019; Gu et al., 2020), thereby reducing emotional exhaustion and depersonalization. Meanwhile, studies showed that long‐term mindfulness meditation training could thicken the cerebral cortex responsible for attention and comprehensive emotions, shrink the amygdala related to fear emotions and strengthen the function of the insula (Seminowicz et al., 2020; Yuan et al., 2020), which lead the individuals to be more positive and optimistic.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing influence of Chinese education, the number of students in China is increasing ( Gu et al, 2020 ). In 2017, China became the leading destination for international students in Asia ( Jianfeng, 2018 ).…”
Section: Introductionmentioning
confidence: 99%